Subchronic toxicity evaluation of leaves from rabbiteye blueberry (Vaccinium virgatum Aiton) in rats - Wataru Tanaka; Daigo Yokoyama; Yasushi Matsuura; Masahiko Nozaki; Naoya Hirozawa; Hisato Kunitake; Masanobu Sakono; Hiroyuki Sakakibara (Toxicology Reports, 2019)
Blueberry leaf may contain multiple compounds with beneficial effects. We conducted a 90-day toxicity study in rats to evaluate the safety of consuming the leaves of rabbiteye blueberry (Vaccinium virgatum Aiton; RB species). Powdered leaves were administered daily by oral gavage at doses of 500, 1000, and 2500 mg/kg body weight to male and female Sprague-Dawley rats for 90 days. Treatment did not result in death or changes in the behavior and external appearance of the animals. No alterations were observed in hematological and serum chemical parameters, urinalysis, food consumption, body weight gain, or absolute and relative organ weights at the end of the treatment period, with the exception of some leukocyte percentages in male rats treated with 500 and 1000 mg/kg blueberry leaf powder. The findings indicate that rabbiteye blueberry leaf is safe for consumption and should be investigated as a candidate functional food. Keywords: Blueberry leaf, No-observed-adverse-effect level (NOAEL), Oral toxicity, Subchronic toxicity, Rat